Sharia Principles in Sharia Capital Market - Rifai, Ahmad (Budapest International Research and Critics University, 2022)
Islamization of the economic sector in this country continues to roll. Since the faucet's opening, which was marked by the establishment of Bank Muamalat, this effort has continued to reach out to the bank and non-bank financial institutions. There are almost no financial institutions left unless they have been touched by the rules of muamalah fiqh. This includes the capital market sector. This paper is included in the literature study. The method used is qualitative by collecting data through information relevant to the topic or problem being studied. The information is obtained from books, research reports, scientific articles, decrees, and written sources, both printed and electronic. The approach taken is descriptive. This approach is used to obtain an overview of answers related to sharia principles in the Islamic capital market. The dynamics and developments above are certainly very encouraging. However, it does not make us complacent. Like other muamalah sectors, the capital market is a very dynamic world and also a bit complicated. Moreover, the law that covers the Islamic capital market is still the same as the conventional capital market law. Therefore, even though there is a formal Islamic capital market, there is still a need to mature concepts and regulations and supervision in the application. Therefore, it is urgent to continue to conduct studies on sharia principles in the capital market so that the dream of the presence of a sharia capital market that accommodates sharia values in a kaffah manner can be realized.